Real-time dynamic singularity avoidance while visual servoing of a dual-arm space robot - Mithun P.; Anurag V.V.; Bhardwaj M.; Shah S.V. (My University, 2025)
Singularity of robotic manipulators is an important issue in the stability and control of autonomous robotic systems. This paper presents a real-time dynamic singularity avoidance approach for such autonomous free-floating space robots where visual servoing is used as feedback in the control loop. The proposed method uses manipulability measure as distance criteria and does not require any prior knowledge of singular configurations. Velocities in task space are projected on a surface of constant manipulability measure to avoid singular configurations. Numerical experiments are carried out, to validate the proposed method, on a 6-Degrees-of-Freedom dual-arm space robot mounted on a service satellite. © 2015 ACM.